An engineered human Fc domain that behaves like a pH-toggle switch for ultra-long circulation persistence - Chang-Han Lee (Nature Portfolio, 2019)
Lee et al. report an engineered IgG1 Fc domain that behaves like an hFcRn binding pH toggle switch. The authors show that this new half-life extension Fc domain confers improved pharmacokinetics in new humanized knock-in mouse strains that recapitulate the key processes for antibody persistence in circulation.